2021
DOI: 10.3389/fpsyt.2021.610171
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Traditional Chinese Herbal Medicine for Antipsychotic-Related Constipation: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background: Constipation is a common but often ignored side effect of antipsychotic treatment, although it is associated with adverse outcomes. The results of the efficacy and safety of traditional Chinese herbal medicine (TCM) in treating constipation are mixed across studies. This is a systematic review and meta-analysis of randomized controlled trials (RCTs) of the efficacy and safety of TCM compared to Western medicine (WM) in treating antipsychotic-related constipation.Methods: Major international electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…At this stage, the application of medications for constipation is still the predominant treatment and can be divided into herbal, Western, and microbial drugs, but the common drugs are still laxatives and prokinetics, which have all been found to have varying degrees of adverse effects in clinical application [ 1 ]. Therefore, it is of great clinical value and urgency to investigate a safe, effective and inexpensive gastrointestinal stimulant based on edible natural plant material for the treatment of chronic functional constipation [ 3 ]. Amomum tsaoko Crevost et Lemarie (AT) is a classic spice commonly used to make soups in Asian countries such as China, Thailand, Burma, and Vietnam.…”
Section: Introductionmentioning
confidence: 99%
“…At this stage, the application of medications for constipation is still the predominant treatment and can be divided into herbal, Western, and microbial drugs, but the common drugs are still laxatives and prokinetics, which have all been found to have varying degrees of adverse effects in clinical application [ 1 ]. Therefore, it is of great clinical value and urgency to investigate a safe, effective and inexpensive gastrointestinal stimulant based on edible natural plant material for the treatment of chronic functional constipation [ 3 ]. Amomum tsaoko Crevost et Lemarie (AT) is a classic spice commonly used to make soups in Asian countries such as China, Thailand, Burma, and Vietnam.…”
Section: Introductionmentioning
confidence: 99%
“…Both alone and in combination with other TCM applications, obvious efficacy without toxic side effects has been observed. In addition, it has been reported that the therapeutic effect of TCM on antipsychogenic constipation was more effective than that of western medicines, such as phenolphthalein and glycerin enema [ 10 ].…”
Section: Introductionmentioning
confidence: 99%